PENGARUH KEGIATAN PRACTICAL LIFE TERHADAP KEMANDIRIAN ANAK USIA 2-3 TAHUN DI BABYBOSS HOUSE KOTA PADANG - Mayshelly, Elza; Serli Marlina; Indra Yeni; Vivi Anggraini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The different degrees of independence seen in the two to three-year-old toddlers at Babyboss House in Padang City served as the impetus for this study.